Norwegian gas exports – assessment of resources and supply to 2035 - Hall, M (Oxford Institute for Energy Studies, 2018)
Norwegian net gas production reached a record high of 122 bcm in 2017, confounding many industry observers who had in 2016 and 2017 been sceptical of the ability of the Norwegian Continental Shelf (NCS) to maintain production at 110-115 bcm. In January 2018, the Norwegian Petroleum Directorate (NPD) made significant upward revisions to its gas production projections which now show output of 121-123 bcm pa from 2018 to 2022, declining to 112 bcm in 2025 and then stabilising at 90-92 bcm pa in 2030-35. This paper examines the reliability of the NPD’s past projections and the plausibility of its updated projections based on published resource data, exploration activity, the capacity of onshore and offshore gas infrastructure, the demand for gas for improved oil recovery and published field development plans. It concludes that the recent revisions reflect a confident appraisal of the resource base and the numerous options for new gas development of existing fields and discoveries. The risk of failing to meet the updated projections to about 2027 appears to be low. Beyond 2027, the projections carry a progressively higher degree of geological, economic and political risk particularly in light of the recent lack of exploration success. By 2035, 30 bcm of the projected 90 bcm of annual gas production is expected to come from currently undiscovered resources. The visibility of future gas production has diminished in recent years because of the reduction in future delivery commitments in Statoil’s gas sales portfolio. However, the reform of its gas sales since 2010 has conferred valuable new flexibility in future upstream investment decisions to develop and market NCS gas resources. The position of Norway as a reliable and competitive supplier of both contracted and flexible gas to NW Europe appears to be secure for the foreseeable future.